2022
DOI: 10.1021/acs.inorgchem.2c01986
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Chemistry and Physics of UCd11

Abstract: In the phase diagram U-Cd, only one compound has been identified so farUCd11 (space group Pm3̅m). Since the discovery of this material, the physical properties of UCd11 have attracted a considerable amount of attention. In particular, its complex magnetic phase diagramas a result of tuning with magnetic field or pressureis not well-understood. From a chemical perspective, a range of lattice parameter values have been reported, suggesting a possibility of a considerable homogeneity range, i.e., UCd11–x. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It has been suggested that among the U–Fe–Si compounds, magnetism is driven predominantly by itinerant electrons. 52 Our preliminary analysis of another newly discovered compound UFe 4 As 2 62 indicates that, much like in UFe 5 As 3 , the uranium 5f orbitals in this system appear to be highly delocalized.…”
Section: Discussionmentioning
confidence: 91%
“…It has been suggested that among the U–Fe–Si compounds, magnetism is driven predominantly by itinerant electrons. 52 Our preliminary analysis of another newly discovered compound UFe 4 As 2 62 indicates that, much like in UFe 5 As 3 , the uranium 5f orbitals in this system appear to be highly delocalized.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to UFe 5 As 3 and related compounds no twinning was observed. 69 Details of the structure determination, atomic parameters and interatomic distances can be found in Tables 2-4. When looking at the refined anisotropic displacement parameters (ADP) of the atoms, Er exhibits a value of 85 pm 2 , which is larger than the…”
Section: Single Crystal X-ray Diffraction and Structure Refinementmentioning
confidence: 99%